PENGARUH PARAFFIN WAX SEBAGAI LAPISAN TANKI PADA AIR CONDITIONER WATER HEATER (ACWH) - Siregar, Chandra Amirsyah Putra; Siregar, A M; Lubis, R D W; Rudi, Arya; Rosyadi, Irham (Jurnal Rekayasa Mesin, 2024)
Currently air conditioner (AC) has been widely developed, one of which is the development of functions into two functions, namely air conditioning and providing hot water for bathing needs. The method is to utilize the high temperature and pressure of the front coming from the compressor, which is diverted into the water tank (air conditioner water heater (ACWH). So that when it passes through the water tank, heat transfer occurs into the water itself. The problem that arises is that when the AC is not operating, there is no heat source to maintain the water temperature in the tank. So an isolation method is really needed. This research will add phase change material such as paraffin wax as a tank lining. The aim is to lengthen the heat transfer process from inside the tank to the environment. Apart from that, this research also aims to analyze the effect of adding paraffin wax as a tank layer on AC performance. This research was carried out experimentally with a test duration of 7 hours, and cooling without time limit until the water temperature in the tank approached ambient temperature. As a result, it was found that adding a layer of paraffin wax as a tank layer was able to lengthen the heat transfer process from inside the tank to the environment. The time difference found was up to 15 hours. Meanwhile, AC performance decreased compared to tank without a paraffin wax coating.